Recovering population of the southern sea otter suppresses a global marine invader - Rikke Jeppesen; Catherine E. de Rivera; Edwin D. Grosholz; M. Tim Tinker; Brent B. Hughes; Ron Eby; Kerstin Wasson (Biological Invasions, 2025)
Understanding the role of apex predators on ecosystems is essential for designing effective conservation strategies. Supporting recovery of apex predators can have many benefits; one that has been rarely examined is control of invasive prey. We investigated whether a recovering apex predator, the southern sea otter ( Enhydra lutris nereis ), can exert local control over a global marine invader, the green crab ( Carcinus maenas ). We determined that southern sea otters in Elkhorn Slough estuary in California can consume large numbers of invasive green crabs and found strong negative relationships in space and time between otter and green crab abundance. Green crabs persisted at highest abundance in this estuary at sites with artificial tidal restriction that were not accessible to otters. Green crab abundance remained lower in this estuary than in all other estuaries in the region, which lack resident sea otters. Conservation organizations and agencies have invested heavily in recovery of southern sea otters, increasing their numbers in this estuary. Restoration of natural tidal exchange, lost marshes, and seagrass beds further support sea otter populations. We have demonstrated that these investments in top predator recovery and habitat restoration have reduced the impacts of a global invader. Our investigation highlights that investment in recovery of top predators can increase beneficial food web interactions and resilience of the entire ecosystem.